Factors influencing return to work in Malaysia: a systematic literature review - Wan Abdullah, Wan Arnidawati; Ng, Eng Eng (2023)
Previous studies have highlighted various factors that contribute to return to work, such as recovery expectations, depression, job satisfaction, stress, gender, age, employer interest, motivation, intervention duration, and type of injury. However, there is a need to synthesize and analyse the existing literature to gain a comprehensive understanding of the considerations specific to the Malaysian context. This systematic literature review aims to identify the influencing factors to return to work among individuals who have experienced work-related injuries or illnesses in Malaysia and explore their implications for policy and practices. The PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) review approach is used for this review. Three digital databases of Google Scholar, SCOPUS, and PubMed databases were searched resulted in 21 related studies. The factors were categorised into four major factors: socio-demographic, psychological and personal, disease and treatment-related and work-related factors. These factors include gender, age, year of injury, industry, job hierarchy, employer interest, motivation, intervention duration, and type of injury. Furthermore, the analysis highlighted various impediments to returning to work, such as a lack of workplace support, insufficient rehabilitation programs, and financial concerns. These findings are substantial for policymakers and practitioners to develop targeted interventions and support systems that address the specific needs of individuals returning to work after work-related injuries or illnesses. By considering these factors, policies and practices can be tailored to improve the likelihood of successful return to work and promote the well-being of employees in Malaysia.